Edukasi Manajemen Keuangan Cerdas: Strategi Menabung dan Investasi Sehat bagi Calon Tenaga Kerja Industri untuk Menghindari Jeratan Pinjaman Online dan Judi Online - Amin Wijoyo; Adrian Martinus Hartono; Ian Marcell Chandra (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aimed to improve the financial literacy of students at SMK Sint Joseph Jakarta through education on personal financial management, saving strategies, healthy investment practices, and the prevention of financial risks associated with illegal online lending and online gambling. The program was conducted through a 120-minute face-to-face session consisting of a pre-test, presentation of educational materials, an interactive quiz using the Kahoot platform, a post-test, and an evaluation questionnaire. The materials covered personal budgeting, income management, prioritizing financial needs, the importance of emergency funds, an introduction to legal investment instruments, and the identification of characteristics of illegal online lending and fraudulent investment schemes. The results indicated an improvement in participants' understanding, as demonstrated by approximately 75% of the students correctly answering the quiz questions. In addition to enhancing participants' knowledge of personal financial management, the program also increased their awareness of making responsible financial decisions as preparation for entering the workforce. Therefore, this PKM program is expected to serve as an effective educational initiative in strengthening the financial literacy of young people while fostering a generation of future workers who are financially responsible, productive, and better prepared to face financial challenges in the digital era.